Knowledge and practice about self-medication for oral health problems among population in Riyadh Region, Saudi Arabia - Inderjit Murugendrappa Gowdar; Meshal Mohammed Alhaqbani; Ahmad Mohammed Almughirah; Saeed Abdullah Basalem; Fahad Ibrahim Alsultan; Mohammed Rashed Alkhathlan (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to know self-medication practices among the population of Riyadh region for oral health issues. Methodology: A questionnaire consisting of demographic self-practice of medication for oral health problems and knowledge about self-medication practices was sent through Google forms and it was in Arabic and English languages. The link of the questionnaire was sent through social and requested to send the link to their friends and relatives. Results: About 50.4% of study participants were having self-practice of medication for oral health problems. Self-practice of medication for oral health issues was statistically significant according to age gender and education (P < 0.05). Toothache (62.4%) is the main problem triggering self-medication and lack of time (44.6%) is the main reason for self-medication. Pain killer (68.8%) was the main medication and antibiotics were used by 2.2% of subjects. Conclusion: Self-medication practice is prevalent in the world and hence, education regarding its consequences and adverse effects for the general public is mandatory.